Digital image correlation for whole field out-of-plane displacement measurement using a single camera - Tay, Cho Jui (2011)
Digital image correlation (DIC) using a single camera has been widely used for inplane displacement and strain measurement. However, in order to obtain out-of-plane displacement, one should employ stereo vision systems which enable multiple directions detection. In this paper, we develop a simple method for whole field out-of-plane displacement measurement using only one camera. The proposed method employs digital image correlation to calculate an apparent in-plane displacement field which is introduced by magnification change due to an unknown out-of-plane displacement. The unknown out-of-plane displacement is subsequently determined from a pinhole camera model and the apparent in-plane displacement. Experiments conducted on a plate, a cantilever beam and a surface with height variation demonstrate that the method is simple, accurate and suitable for measurement of non-structured objects.